Molecular Control of Carpel Development in the Grass Family - Shen, Chaoqun; Li, Gang; Dreni, Ludovico; Zhang, Dabing (Frontiers in Plant Science, 2021)
Carpel is the ovule-bearing female reproductive organ of flowering plants, and is required to ensure its protection, an efficient fertilization, and the development of diversified types of fruits, thereby it is a vital element of most food crops. The origin and morphological changes of the carpel are key to the evolution and adaption of angiosperms. Progresses have been made in elucidating the developmental mechanisms of carpel establishment in the model eudicot plant Arabidopsis thaliana, while little and fragmentary information is known in grasses, a family that includes many important crops such as rice (Oryza sativa), maize (Zea mays), barley (Hordeum vulgare) and wheat (Triticum aestivum). Here, we highlight recent advances in understanding the mechanisms underlying potential pathways of carpel development in grasses, including carpel identity determination, morphogenesis and floral meristem determinacy. The known role of transcription factors, hormones and miRNAs during grass carpel formation is summarized and compared with the extensively studied eudicot model plant Arabidopsis. The genetic and molecular aspects of carpel development which are conserved or diverged between grasses and eudicots are therefore discussed.